(إنِ) المخففة من الثقيلة في القرآن الكريم((دراسة نحوية)) (University of Mosul-college of Basic Education, 2008)
من أنواع (إنِ) المكسورة الهمزة الساكنة النون : المخففة من الثقيلة ، وهي بمعنى الثقيلة حرف توكيد ، إلاَّ أنَّها تختلف عنها بأنَّها مهملة في الغالب ، وليست عاملة كالثقيلة ، وأنها تدخل على الجملة الفعلية والاسمية ، بخلاف الثقيلة التي يقتصر دخولها على الجملة الاسميةOne of kinds of (en) is the lightened from dark which means dark litter of assurance , It is different from the dark because it is neglected almost .and it is not functional as the dark It enters on the verbal and nominal phrases in contradiction to the dark which enters only on nominal phrases.